KORELASI SIKAP KEMANDIRIAN SISWA DENGAN TUGAS PRODUK SISWA PADA PEMBELAJARAN BIOLOGI DI SMAN 1 KELAS XI KOTA PEKANBARU - Suci Wulandari; Darmawati Darmawati; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to produce a Correlation of Student Self-Reliance Attitudes With the Tasks of Student Products on Biology Learning at SMAN 1 Class XI Pekanbaru City.This research was conducted at at SMAN 1 Pekanbaru in class XI in October 2017 until November 2017. This research is a descriptive research with correlational study type. The sample in this research is 35 students of class XI academic year 2017/2018. Sample determination was by random sampling using lottery technique. The research instrument used is a closed questionnaire consisting of 30 statements and 6 indicators of dependence on others, self-confidence, self-control, discipline, motivation, responsibility and the value of product tasks from biology subject teachers. Data collection is by spreading questionnaire to students to know the attitude of student independence to the task of product class XI in SMA Negeri 1 Pekanbaru. The results showed that there is a strong correlation between the attitude of independence with the tasks of student products in SMAN 1 Class XI Pekanbaru. So for high school biology teachers / equivalent to keep applying the product assignment in accordance with the material taught in a sustainable manner so as to guide students in helping the attitude of independence well in the implementation of learning.Key Words: Correlation, independence, product tasks